MORPHOLOGICAL AND STRUCTURAL FEATURES OF STENOTIC LESIONS OF THE TRACHEA AND BRONCHI, BRONCHIOLECTATIC EMPHYSEMA, AND TRACHEOESOPHAGEAL FISTULAS - Polvonnazirova Farangiz Oybek qizi (Web of Journals Publishing, 2025)
Congenital and early developmental bronchopulmonary malformations are frequently characterized by structural defects within the bronchiolar wall, most notably involving the smooth muscle layer. Hypoplasia or aplasia of these muscular elements results in both functional and morphological disturbances, manifesting as abnormal dilatation of the bronchioles. This pathological process plays a critical role in the formation of centrilobular emphysema, particularly in its Leschke variant. Moreover, insufficient maturation of the mucosal lining and smooth muscle framework reduces airway stability, thereby predisposing the respiratory bronchioles to emphysematous transformation. Such anatomical and functional insufficiencies create a favorable environment for recurrent respiratory infections. Over time, secondary inflammatory changes become predominant, commonly progressing to bilateral, multisegmental bronchopneumonia. Pathological examination frequently identifies alterations in pulmonary segments 2, 6, 7, 8, 9, and 10 adjacent to the hilar region. These sites often demonstrate compact foci of mixed exudative inflammation, areas of atelectasis, and emphysematous changes. Recognition of these morphologic alterations is fundamental for elucidating the pathogenesis of post-bronchopneumonic complications, and they remain critical for precise diagnosis and optimized therapeutic strategies. The present investigation focuses on the pathomorphological characteristics of bronchiolectatic emphysema, tracheoesophageal fistulas, and stenotic lesions of the trachea and bronchi, with particular emphasis on their clinical significance and diagnostic implications.
Keywords: Bronchiolectasis, Leschke emphysema, tracheal stenosis, bronchial stenosis, tracheoesophageal fistula, pathomorphology, airway deformation, respiratory bronchioles, bronchopneumonia.